Metody badania lojalności konsumentów na europejskim rynku usług finansowych - Smyczek, Sławomir (Methods of Customers' Loyalty Research on the European Market of Financial Services, 2006)
Loyal customers assure operation and development of financial institutions on the internal European market. In order to identify a level and a structure of customers' loyalty, financial institutions need appropriate method of research. This method should make possible international comparisons of information, results of conducted research, reduction of research costs as well realisation and control improvement of research on the European market. The method which fits t those criteria is TRI*M. This method enables financial institutions to measure satisfaction, confidence and attachment of customers. It also provides institutions to level and factors determining consumer loyalty in a synthetic way.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 277-284